Taxes, Tunneling and Exchange Rate on Transfer Pricing Decisions - Mulyani, Hani Sri; Prihartini, Endah; Afipah, Asmi; Ghassani, Alya (Journal of International Conference Proceedings, 2023)
The purpose of this study is to determine transfer pricing in companies in the manufacturing sector. This topic was adopted from several theoretical studies and previous studies which were combined as a factor influencing transfer pricing. This research methodology uses an associative causal approach. In taking the research sample using a purposive sampling technique and obtained 100 companies in the Manufacturing sector that were listed on the Indonesia Stock Exchange for the 2018-2022 period. The data analysis technique is in the form of logistic regression with SPSS 25. The results show that only taxes have an effect on transfer pricing. Meanwhile, tunneling and exchange rate variables have no significant effect on transfer pricing. We recommend future research agenda related to transfer pricing. Most of the previous studies only used the tax variable as a whole and no one had detailed it. However, an overall and complete description of these factors along with the specifications of the determinants of transfer pricing are the targets of our research.